Peran Skor Kalsium Arteri Koroner sebagai Penanda Sistemik Aterosklerosis: Studi Pencitraan Potong Lintang - Aulia, Mohammad Sidqi; Kusumawardhani, Nuraini Yasmin; Hidayat, Syarief; Pranata, Raymond (Jurnal Kardiologi Indonesia, 2025)
Background. Coronary Artery Calcium Score (CACS) is widely used to assess coronary atherosclerosis. However, its utility in reflecting systemic atherosclerosis burden remains limited. Notably, no prior study has investigated the relationship between CACS and plaque morphology in the lower extremities. This study aimed to address this gap by examining the association between CACS, ankle-brachial index (ABI), and peripheral arterial plaque morphology as assessed by duplex ultrasonography. Methods. This single-center, cross-sectional study enrolled 100 consecutive patients who underwent coronary CT angiography and lower extremity Doppler ultrasound between November 2024 and May 2025. CACS was calculated using Agatston method. ABI and Doppler-based plaque morphology were evaluated to determine the presence, severity, and complexity of peripheral artery disease (PAD). Results. A moderate inverse correlation was found between CACS and ABI (r = -0.628, p < 0.001), while a moderate positive correlation was observed between CACS and plaque morphology (r = 0.619, p <0.001). CACS showed good discriminatory power for detecting peripheral plaque (AUC = 0.765), and excellent performance in identifying advanced plaque types (III-IV) at a threshold of 478.5 HU (AUC = 0.852; sensitivity 68%; apecificity 91.7%). Conclusion. This is the first study to demonstrated a direct association between coronary calcium burden and plaque morphology in the lower extremities. These findings highlight the potential role of CACS as a surrogate marker for systemic atherosclerosis and a valuable tool for identifying asymptomatic individuals who may benefit from peripheral arterial evaluation.